Effects of a Future Time Perspective–Based Career Intervention on Career Decisions. (February 2020) - Park, In-Jo; Rie, Juil; Kim, Hyang Sook; Park, Jiyoung
The purpose of the present study was to examine the effects of a future time perspective (FTP)-based career intervention on career decisions. The career intervention consisted of three sessions based on three factors of FTP: opportunity, value, and connectedness. The study was performed with 41 college students who were randomly assigned to the intervention group ( N = 21) and the control group ( N = 20). The intervention group showed higher levels of FTP, career decision-making self-efficacy, and career search self-efficacy at the posttest compared to the corresponding results of the control group. Furthermore, the results of a paired-samples t test showed that the effects of the career intervention were maintained at a 4-week follow-up. Lastly, the theoretical and practical implications of the study were discussed.